2018
DOI: 10.1016/j.yexcr.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of Fam20c altered cell behaviors and BMP signaling of immortalized dental mesenchymal cells

Abstract: FAM20C mutations compromise the mineralization of skeleton and tooth in both human and mouse. Putatively, the mineralization disorder is attributed to the elevated fibroblast growth factor 23 (FGF23), which reduced the serum phosphorus by suppressing the reabsorption of phosphorus in kidney. Besides the regulation on systemic phosphorus homeostasis, FAM20C was also implicated to regulate cell behaviors and gene expression through a cell-autonomous manner. To identify the primary effects of Fam20c on dental mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…We observed that reduced FAM20A is associated with compromised cellular behaviours, including impaired proliferation, attachment, spreading, migration, and colony formation in DDP. These findings align with previous findings showing that Fam20c deficiency in mouse dental mesenchymal cells resulted in suppressed proliferation, mobility, and wound healing (Liu, Zhou, et al., 2018). Similarly, FAM20C knockout in osteoblast cell lines presented reduced cell proliferation, adhesion, migration, and colony (Geng et al., 2022; Liu, Zhang, et al., 2018; Tagliabracci et al., 2015).…”
Section: Discussionsupporting
confidence: 93%
“…We observed that reduced FAM20A is associated with compromised cellular behaviours, including impaired proliferation, attachment, spreading, migration, and colony formation in DDP. These findings align with previous findings showing that Fam20c deficiency in mouse dental mesenchymal cells resulted in suppressed proliferation, mobility, and wound healing (Liu, Zhou, et al., 2018). Similarly, FAM20C knockout in osteoblast cell lines presented reduced cell proliferation, adhesion, migration, and colony (Geng et al., 2022; Liu, Zhang, et al., 2018; Tagliabracci et al., 2015).…”
Section: Discussionsupporting
confidence: 93%
“…PRKCA, another hub gene, was demonstrated to regulate bone architecture and osteoblast activity (Galea et al, 2014). FAM20C encodes a family member of secreted protein kinases, which can bind calcium and phosphorylate proteins involved in bone mineralization (Liu et al, 2018). RBPJ, a primary nuclear mediator of Notch signaling, has also been associated with osteogenesis (S3) (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a large body of literature, focusing on conditional tissue-specific knockout mice and cell models, reports the roles of Fam20C in promoting biomineralization including the growth and development of osteoblasts, osteoclasts, bone, dentin, and enamel ( Fig. 5 ) ( 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ).…”
Section: Fam20c the Secreted Golgi Casein Kinasementioning
confidence: 99%